Treatment of Lupus Nephritic with Severe Preeclampsia: A Case Report - Asri Insanur Rahma; Lita Diah Rahmawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
A 25 years-old pregnant woman with history of Systemic Lupus Erythematosus (SLE) complained shortnessof breathing and swelling legs. Physical examination showed hypertension, tachycardia, tachypnea,anemic conjunctiva, and pitting edema in both legs. Workup examination found anemia, hypoglycemia,hypoalbuminemia, proteinuria, metabolic acidosis, strong positive dsDNA, trivial MR, mild TR, PR, dilatedLV, decrease of LV systolic function, hypokinetic global LV, eccentric LVH, and severe oligohydramnios.The patient was diagnosed with severe preeclampsia, severe oligohydramnios, SLE, Lupus Nephritic (LN),stage II JNC VII hypertension, and peripartum cardiomyopathy.An emergency caesarean section was planned as the main management to prevent infant and maternalmorbidity and mortality. MgSO4 was given to prevent eclampsia. Methylprednisolone and azathioprinewere given to control SLE and LN activity. Furosemide, spironolactone, ramipril, methyldopa and nifedipinewere given to control blood pressure, help normalizing heart function, and prevent organ failure. The patientwas suggested to postpone next pregnancy until 1 year after LV function turns to normal.